Composition-dependent emission linewidth broadening in lead bromide perovskite (APbBr3, A = Cs and CH3NH3) nanoparticles. Issue 5 (15th January 2018) - Ham, Sujin; Chung, Heejae; Kim, Tae-Woo; Kim, Jiwon; Kim, Dongho
Abstract : We explore composition-dependent emission linewidth broadening in lead bromide perovskite nanoparticles. The results provide insight into the development of light-emitting diodes with high color purity. Abstract : Lead halide perovskite nanoparticles (NPs) are attractive as they exhibit excellent color purity and have a tunable band gap, and can thus be applied in highly efficient photovoltaic and light-emitting diodes. Fundamental studies of emission linewidth broadening due to spectral shifts in perovskite NPs may suggest a way to improve their color purity. However, the carrier-induced Stark shift that causes spectral diffusion still requires investigation. In this study, we explore composition-related emission linewidth broadening by comparingCsPbBr3 and CH3 NH3 PbBr3 (MAPbBr3 ) perovskite NPs. We find that theMAPbBr3 NPs are more sensitive to fluctuations in the local electric fields than theCsPbBr3 NPs due to an intrinsic difference in the dipole moment between the two A cations (Cs and MA), which shows a carrier-induced Stark shift. The results indicate that the compositions of perovskite NPs are closely associated with emission linewidth broadening and they also provide insights into the development of NP-based devices with high color purity.